Analysis of Performance and Safety Risks in the Nickel Mining Sector - Amirudin, Agus; Sukwika, Tatan; Ramli, Soehatman (Indonesian Journal of Global Health Research, 2024)
Mining safety performance refers to evaluating the effectiveness and efficiency of efforts made to maintain the safety and health of workers in the mining environment.The aim of this research is to analyze the performance and safety risks in the nickel mining sector at PT. Putra Perkasa Abadi Job Site MLP Southeast Sulawesi. This type of research is a mixed method which begins with quantitative research and continues with qualitative research. The research subjects/respondents in this study were 653 people. Risk analysis uses bow tie analysis. The data collection method for assessing the level of mining safety performance consists of several methods, namely document review, questionnaire distribution, data analysis, interviews, observations, focus group discussions, and simulations.The mine worker participation indicator is at a proactive level with an achievement value of 0.13. Indicators of Responsibility of Work Unit Leaders; Accident statistics are at a proactive level with an achievement value of 0.32. The statistical indicators for accidents, dangerous events, incidents resulting from occupational diseases and occupational diseases are at the planned level with an achievement value of 0.17. The Control Efforts indicator is at a proactive level with an achievement value of 0.26. Based on the recapitulation results of all the Company's Mining Safety Performance indicators it is at the Proactive level with a value of 0.88. PT. PPA Job Site MLP has mining performance at a proactive level. This shows that this company is starting to involve workers in the improvisation stage of K3 management.